Geographical Analysis of The Characteristics of Fluctuation of Temperatures and The Rainfall in Dokan District - Ashty Salam Sdiq; Hawre Peshraw Tawfeeq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The study is entitled “Geographical analysis of the characteristics of fluctuation of temperatures and the rainfall in Dokan district", where two key elements of the climate (temperature and rainfall) were taken between 2001 and 2020, on which we relied at three weather stations, including at Dokan stations, Koya, Chamchmal), The importance of this research is to show the rapid disruption that occurred in both the temperature and rain elements in order to show its effects on the model and climate direction in the research area, and to reach the research goal we divided the research into four main parts: part one: high temperature levels and the amount of rain.Part 2: Models of climate rise in the Dokan region, part 3 towards rising weather in the Dokan region, Part 4: Climate trend in the Dokan region) And at the end of the study they concluded that rising temperatures and rainfall were one of the atmospheric characteristics of the research area and had an impact on the climate direction of the research area.